British romanticism and Italian literature : translating, reviewing, rewriting - Bandiera, Laura; Saglia, Diego (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft ;, 2005)
Drawing on a long-standing tradition of fictional images, British writers of the Romantic period defined and constructed Italy as a land that naturally invites inscription and description. In their works, Italy is a cultural geography so heavily overwritten with discourse that it becomes the natural recipient of further fictional transformations. If critics have frequently attended to this figurative complex and its related Italophilia, what seems to have been left relatively unexplored is the fact that these representations were paralleled and sustained by intense scholarly activities. This v.